An improved deterministic truncation of Monte Carlo solution for pin-resolved nuclear reactor analysis. (February 2022) - Kim, Inhyung; Kim, Yonghee
Highlights: An DTMC method is developed for the acceleration of the MC neutronic analysis. Strategies for inactive cycles are suggested using Buffon's probability and entropy. The real variance of the iDTMC is estimated by a sampling scheme in a single MC run. The iDTMC can have 30–50 times higher FOMs at the 1st cycle compared to standrard MC. Abstract: An improved deterministic truncation of Monte Carlo (iDTMC) solution method has been developed for acceleration and variance reduction of Monte Carlo (MC) neutronic analysis. A new calculational strategy has been applied by taking advantages of partial-current-based coarse mesh finite difference (p-CMFD) method with two different mesh sizes in a tactical way. Fast convergence of source distribution is attained by a coupled assembly-wise p-CMFD method in inactive cycles, and detailed deterministic solutions are obtained by a decoupled pin-wise p-CMFD method in active cycles. Assistant schemes are also devised to enhance efficiency of the iDTMC method, which include one-node p-CMFD acceleration, new inactive cycle strategy, and real variance estimation method for iDTMC solutions. The iDTMC method is evaluated in a small reactor and a big-size one. The iDTMC solutions are compared with those of the p-CMFD accelerated MC calculation, and they are appraised in terms of source convergence, computing time, and figure-of-merit.